1997
DOI: 10.1080/09595239700186791
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to preventing alcohol‐related problems: the experience of New Zealand and Australia

Abstract: New Zealand and Australia have experienced similarities in their drinking cultures and patterns since colonization. This paper briefly reviews those experiences and looks at the approaches both countries have taken in dealing with alcohol-related problems. Over 10 years ago Australia developed a national strategy embracing a harm reduction approach and more recently New Zealand embarked upon a similar process. As well as examining the development of these, other initiatives are examined. These include approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Maori were initially introduced to alcohol in the early 1800s by European settlers, whalers and other immigrants (Stewart 1997). Unlike most other nations, Maori did not have experience with any form of alcohol before this time (Hutt 1999;Mancall et al 2000;Park 1995).…”
Section: History Of Alcohol Use Amongst Maorimentioning
confidence: 99%
“…Maori were initially introduced to alcohol in the early 1800s by European settlers, whalers and other immigrants (Stewart 1997). Unlike most other nations, Maori did not have experience with any form of alcohol before this time (Hutt 1999;Mancall et al 2000;Park 1995).…”
Section: History Of Alcohol Use Amongst Maorimentioning
confidence: 99%
“…Of the options offered, we prefer Babor' s suggestion of an earmarked tax on alcohol (which is how some of the alcohol research we carry out is funded). While the history of New Zealand' s Alcohol Advisory Council shows that such funding systems are not immune from industry in¯uence in the right political climate (Stewart, 1997), funding from an earmarked tax provides some structural independence where direct industry-funded research does not.…”
Section: Con¯ict Of Interestmentioning
confidence: 99%
“…In New Zealand and Australia, liberal central government alcohol policies have led to increased alcohol availability and promotion since the 1990s, and communities are increasingly relying upon local policies and community action to address alcohol‐related problems (e.g., Casswell & Maxwell, ; Maclennan, Kypri, Langley, & Room, ; Duigan & Casswell, ; Maclennan, Kypri, Room, & Langley, ; Stewart, ). Recent research has found strong public support among New Zealanders for local governments to restrict the hours of operation of on‐licensed premises, to use liquor bans to control drinking in public places, and for local governments and police to be stricter in their enforcement of drinking laws (Maclennan et al, ) and researchers are beginning to examine barriers to adopting local alcohol policies, such as legislative boundaries set by central government and special‐interest groups becoming involved in local policy agendas (Maclennan et al, ).…”
Section: Effective Interventions and Policies At The Local Levelmentioning
confidence: 99%
“…Likewise, Australia and New Zealand have experienced similar challenges when central laws were relaxed. National policies in New Zealand and Australia are highly influenced by the alcohol industry perspective and focus on harm reduction strategies to reduce excessive and hazardous alcohol use in specific settings and within at‐risk groups, rather than the population‐based strategy that is used to reduce the prevalence of tobacco use in both countries (e.g., Stewart, ).…”
Section: Challengesmentioning
confidence: 99%